Sulphur-bearing and complex organic molecules in an infrared cold core. Issue 1 (30th October 2019) - Beaklini, Pedro P B; Mendoza, Edgar; Canelo, Carla M; Aleman, Isabel; Merello, Manuel; Kong, Shuo; Navarete, Felipe; Janot-Pacheco, Eduardo; Abraham, Zulema; Lépine, Jacques R D; de Almeida, Amaury A; Friaça, Amâncio C S
ABSTRACT: Since the start of ALMA (Atacama Large Millimeter Array) observatory operation, new and important chemistry of infrared cold core was revealed. Molecular transitions at millimetre range are being used to identify and to characterize these sources. We have investigated the 231 GHz ALMA archive observations of the infrared dark cloud region C9, focusing on the brighter source that we called as IRDC-C9 Main. We report the existence of two substructures on the continuum map of this source: a compact bright spot with high chemistry diversity that we labelled as core, and a weaker and extended one, that we labelled as tail. In the core, we have identified lines of the molecules OCS(19−18), 13 CS(5−4), and CH3 CH2 CN, several lines of CH3 CHO and the k-ladder emission of 13 CH3 CN. We report two different temperature regions, while the rotation diagram of CH3 CHO indicates a temperature of 25 K, the rotation diagram of 13 CH3 CN indicates a warmer phase at temperature of ∼450 K. In the tail, only the OCS(19−18) and 13 CS(5−4) lines were detected. We used the nautilus and the radex codes to estimate the column densities and the abundances. The existence of hot gas in the core of IRDC-C9 Main suggests the presence of a protostar, which is not present in the tail.